Implementasi Pendidikan Anak Usia Dini (Paud) Perspektif Pendidikan Islam - M. Suyuti Yusuf (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2023)
The research aims to analyze the dynamics of early childhood education, implementation of early childhood education, supporting and inhibiting factors for the implementation of early childhood education and the solution from the perspective of Islamic education. This research uses a qualitative approach with a case study type. The result is that the implementation of PAUD in the city of Palopo is carried out according to the rules. The quantity and quality are inadequate, due to a lack of facilities and infrastructure as well as teaching staff. Problems with implementing early childhood education in the city of Palopo include: Many parents of students still do not understand the importance of early childhood education, parents of students do not understand informal, non-formal and formal education, teachers who teach in PAUD institutions do not meet the qualifications academics, and scientific disciplines, the government's attention to the importance of early childhood education is still low. The solutions offered are: providing parents with an understanding of the importance of Early Childhood Education for child development, the need to increase the qualifications and competence of human resources in early childhood education institutions, and increase government involvement in the management of Early Childhood Education institutions. Keyword: Implementation, PAUD, Islamic Education